MUSLIM FAMILIES AND RELIGIOUS RESOURCES IN DEVELOPING PARENTAL ACCEPTANCE OF CHILDREN WITH DISABILITIES - Suharsiwi Suharsiwi; Weny Savitry Pandia (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
Parental acceptance is a crucial component of family adaptation and psychological well-being in families of children with disabilities. This study aims to examine the role of Muslim family environments and religious attitude (RA) in shaping parental acceptance of children with disabilities within a religiously embedded cultural context. Using a quantitative correlational design, data were collected from 77 parents of children with disabilities in Indonesia. The study focuses on key family-based factors, including parental understanding, social support, and Islamic religious beliefs as significant contributors to parental acceptance. The findings reveal that parental understanding (β = .34), Religious Attitude (RA) (β = .29), and social support (β = .25) significantly predict parental acceptance, jointly explaining 48% of the variance. These results indicate that parental acceptance is not solely determined by cognitive factors but is also shaped by social and faith-based resources within Muslim family environments. Islamic values, such as patience (ṣabr – صَبْر), gratitude (shukr – شُكْر), and trust in God (tawakkul – تَوَكُّل), provide meaningful frameworks that support parents in interpreting and accepting their child’s condition. The study implies that integrating Islamic values, strengthening parental understanding, and enhancing social support systems can contribute to more adaptive family processes and improved well-being among families of children with disabilities.